2021
DOI: 10.1136/bmjopen-2021-050380
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional survey on physician burnout during the COVID-19 pandemic in Vancouver, Canada: the role of gender, ethnicity and sexual orientation

Abstract: ObjectiveTo determine the prevalence of physician burnout during the pandemic and differences by gender, ethnicity or sexual orientation.Design, setting and participantsWe conducted a cross-sectional survey (August–October in 2020) of internal medicine physicians at two academic hospitals in Vancouver, Canada.Primary and secondary outcomesPhysician burnout and its components, emotional exhaustion, depersonalisation and personal accomplishment were measured using the Maslach Burnout Inventory.ResultsThe respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 33 publications
7
97
0
3
Order By: Relevance
“…Nevertheless, being at front lines fighting the battle against the COVID-19 pandemic, the HCWs are subjected to long working hours, exhaustion and as our review shows, a high burnout prevalence (Sunjaya et al, 2021 ; Tan et al, 2020 ). The studies generally reported HCWs who had direct contact with COVID-19 patients to be more likely at risk of being burnout, in line with other studies in other regions including Canada (Khan et al, 2021 ) and US (Kannampallil et al, 2020 ). Considering the current situation of the pandemic in which the majority of the SEA countries are grappling with record breaking cases, deaths and hospitalizations exacerbated with a slow and low vaccination process, the HCWs are at a greater risk of adverse mental effects.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, being at front lines fighting the battle against the COVID-19 pandemic, the HCWs are subjected to long working hours, exhaustion and as our review shows, a high burnout prevalence (Sunjaya et al, 2021 ; Tan et al, 2020 ). The studies generally reported HCWs who had direct contact with COVID-19 patients to be more likely at risk of being burnout, in line with other studies in other regions including Canada (Khan et al, 2021 ) and US (Kannampallil et al, 2020 ). Considering the current situation of the pandemic in which the majority of the SEA countries are grappling with record breaking cases, deaths and hospitalizations exacerbated with a slow and low vaccination process, the HCWs are at a greater risk of adverse mental effects.…”
Section: Discussionsupporting
confidence: 82%
“…141 This concern is also supported by a survey of 131 physicians and nurses in a Montreal hospital where the intention to quit was reported by 50% of nurses and 20% of physicians and a survey of 257 physicians in Vancouver of whom 21% were considering quitting. 104,113 In a Toronto hospital in Spring 2021, 30% of nurses and 13% of physicians surveyed reported considering leaving their jobs, specifically because of moral distress (Hunter J, personal communication). Observation indicates that professionals are acting on their intention to leave.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 250 internal medicine specialist physicians in two Vancouver hospitals conducted from August to October 2020, found a prevalence of severe emotional exhaustion (MBI-EE >26) of 63%. 104 A longitudinal survey of a single cohort of 422 staff representing diverse roles (nurses, doctors, professionals of other disciplines, support services, researchers, learners etc.) in a downtown Toronto hospital repeated three times at three-month intervals from November 2020 to May 2021 found high and rising burnout.…”
Section: Covid-19 Has Exacerbated Risk Factors For Burnout and Increased Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“… Setiawati et al, 2021 , Soh et al, 2020 , Sujadi et al, 2021 , Sun et al, 2021 , Sunjaya et al, 2021 , Tee et al, 2020 , Tee et al, 2020 , Vigo et al, 2021 , Wang et al, 2021 , Chew et al, 2020 , WHO 2020 , Wong et al, 2020 , Woon et al, 2020 , Chew et al, 2020 , Yadav et al, 2021 , Ye et al, 2020 , Chow et al, 2021 , Dai et al, 2020 , Dong and Zheng, 2020 , Ettman et al, 2020 , Fauzi et al, 2021 , Cénat et al, 2020 , Hsieh et al, 2021 , Huang and Zhao, 2021 , Kannampallil et al, 2020 , Khan et al, 2020 , Khan et al, 2021 , Lai et al, 2020 , Lee et al, 2020 , Li et al, 2021 , Li et al, 2021 , Liao et al, 2021 , Lim et al, 2020 , Liu et al, 2021 , Liu et al, 2021 , Chen et al, 2021 , Liu et al, 2021 , Mohd Noor et al, 2021 , NICE 2009 , Chen et al, 2021 , Pak et al, 2020 , Person et al, 2004 , Chen et al, 2021 , Pierce et al, 2020 , Pramukti et al, 2020 , Rahman, 2021 , Roslan et al, 2021 …”
Section: Uncited Referencesmentioning
confidence: 99%